2007
DOI: 10.1051/parasite/2007144335
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofCryptosporidiumspp. (Eucoccidiorida: Cryptosporiidae) in seven species of farm animals in Tunisia

Abstract: Summary :1,001 faecal samples were obtained from 89 sheep (lambs and adult), 184 goats, 190 horses, 178 rabbits, 110 camels, 200 broiler chicken and 50 turkeys housed in farms from different localities in Tunisia. All samples were analysed for Cryptosporidium oocysts by microscopic examination of smears stained by modified Ziehl Neelsen technique. The parasite was detected in ten lambs and adult sheep (11.2 %) and nine broiler chicken (4.5 %). Molecular characterization, performed in four animals, identified C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
4
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 21 publications
8
38
4
6
Order By: Relevance
“…However, most reports on the prevalence in chickens were published in the 1980s and 1990s, with infection rates ranging from 4.5 to 50% depending on the location and the methods used in detection (de Graaf et al, 1999). In contrast, in the past 10 years there have been only about six reports (Trampel et al, 2000;Kimura et al, 2004;Huber et al, 2007;Soltane et al, 2007;Shemshadi et al, 2010;Smith et al, 2010). Likewise, there are only a few reports (about seven) concerning Cryptosporidium infections in ducks (Mason, 1986;Richter et al, 1994;O'Donoghue, 1995;Morgan et al, 2001;Kuhn et al, 2002;Huber et al, 2007;Amer et al, 2010).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, most reports on the prevalence in chickens were published in the 1980s and 1990s, with infection rates ranging from 4.5 to 50% depending on the location and the methods used in detection (de Graaf et al, 1999). In contrast, in the past 10 years there have been only about six reports (Trampel et al, 2000;Kimura et al, 2004;Huber et al, 2007;Soltane et al, 2007;Shemshadi et al, 2010;Smith et al, 2010). Likewise, there are only a few reports (about seven) concerning Cryptosporidium infections in ducks (Mason, 1986;Richter et al, 1994;O'Donoghue, 1995;Morgan et al, 2001;Kuhn et al, 2002;Huber et al, 2007;Amer et al, 2010).…”
Section: Introductionmentioning
confidence: 89%
“…In European countries such as Scotland and Greece, the infection rates in broilers were 18.7% (26/139) and 24.3% (17/70), respectively (Randall, 1982;Papadopoulou et al, 1988). In Africa, 24% (54/225) and 4.5% (9/200) prevalence rates were reported in Morocco and Tunisia, respectively (Kichou et al, 1996;Soltane et al, 2007). In Japan and Iran, rates of 33.3% (4/12) and 23.8% (57/152) were observed, respectively, in broiler chickens (Itakura et al, 1984;Shemshadi et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Like C. parvum, C. meleagridis appears to have a large host range and has been described from a wide range of avian species including turkeys, parrots, chickens, cockatiels and a red-legged partridge (O'Donoghue, 1995, Morgan, et al, 2000b, Darabus and Olariu, 2003, Abe and Iseki, 2004Huber et al, 2007;Pagès-Manté et al, 2007;Soltane et al, 2007). Experimental transmission studies have shown that C. meleagridis can infect broiler chickens, ducks, turkeys, calves, pigs, rabbits, rats, mice (O'Donoghue, 1995, Darabus and Olariu, 2003, Huang, et al, 2003.…”
Section: Cryptosporidium Meleagridis Slavin 1955mentioning
confidence: 99%
“…A ocorrência de criptosporidiose em rebanhos ovinos foi descrita em várias regiões geográficas, com incidências variáveis: 10,1% na Polônia (MAJEWSKA et al, 2000), 59% na Espanha (CAUSAPÉ et al, 2002), 77,4% nos Estados Unidos (SANTÍN; TROUT; FAYER, 2007), 11,2% na Tunísia (SOLTANE et al 2007); 24,5% na Austrália (YANG et al, 2009), também 25% (SILVA, 2007, 41% (COSENDEY et al, 2008), 6,7 % (FÉRES et al, 2009), 0% (SEVÁ et al, 2010, 1,6% (FIUZA et al, 2011), 15% (ZUCATTO, 2013 Wang et al (2010), obtiveram três espécies de Cryptosporidium, pela PCR, sendo C. andersoni em ovelhas gestantes e no pós-parto (04/82); C. xiaoi em cordeiros durante e após desmame (04/82) e C. genótipo cervine em amostras de cordeiros e ovelhas (74/82).…”
Section: Criptosporidiose Em Ovinosunclassified